Stable and non-toxic ultrasmall gadolinium oxide nanoparticle colloids (coating material = polyacrylic acid) as high-performance T1 magnetic resonance imaging contrast agents. Issue 6 (16th January 2018) - Miao, Xu; Ho, Son Long; Tegafaw, Tirusew; Cha, Hyunsil; Chang, Yongmin; Oh, In Taek; Yaseen, Ahmad Mohammad; Marasini, Shanti; Ghazanfari, Adibehalsadat; Yue, Huan; Chae, Kwon Seok; Lee, Gang Ho
Abstract : Stable and non-toxic ultrasmall Gd2 O3 nanoparticle colloids as high-performance T 1 MRI-CA were developed. Abstract : For use as positive ( T 1 ) magnetic resonance imaging contrast agents (MRI-CAs), gadolinium oxide (Gd2 O3 ) nanoparticle colloids ( i.e. nanoparticles coated with hydrophilic ligands) should be stable, non-toxic, and ultrasmall in particle diameter for renal excretion. In addition, they should have a high longitudinal water proton relaxivity ( r 1 ) and r 2 / r 1 ratio that is close to one ( r 2 = transverse water proton relaxivity) for high-performance. In this study, we report ultrasmall Gd2 O3 nanoparticle colloids [coating material = polyacrylic acid, M w = ∼5100 Da] satisfying these conditions. The particle diameter was monodisperse with an average value of 2.0 ± 0.1 nm. The colloidal suspension exhibited a high r 1 value of 31.0 ± 0.1 s −1 mM −1 and r 2 / r 1 ratio of 1.2, where r 1 was ∼8 times higher than that of commercial Gd-chelates: the cooperative induction model was proposed to explain this. The effectiveness of the colloidal suspension as a high-performance T 1 MRI-CA was confirmed by taking in vivo T 1 MR images in a mouse after intravenous administration. Highly positive contrast enhancements were observed in various organs of the mouse such as the liver, kidneys, and bladder. The colloidal suspension was then excreted through the bladder.